Predictive value of NLR and PLR in response to preoperative chemotherapy and prognosis in locally advanced gastric cancer - Wang, Wentao; Tong, Yilin; Sun, Shulan; Tan, Yuen; Shan, Zexing; Sun, Fan; Jiang, Chengyao; Zhu, Yanmei; Zhang, Jianjun (Frontiers in Oncology, 2022)
Purpose: Pretreatment neutrophil-to-lymphocyte (NLR) and platelet-to-lymphocyte (PLR) ratios are markers of systemic inflammation. In patients with locally advanced gastric cancer (GC), the utility of these ratios in predicting tumor regression grade (TRG) after neoadjuvant chemotherapy (NCT) remains unclear. Methods: This retrospective study examined 283 locally advanced GC patients who underwent NCT and radical surgery. Receiver operating characteristic (ROC) curve analysis and Youden index were applied to identify optimal NLR/PLR cutpoints; Kaplan-Meier method was used to estimate overall survival (OS) and disease free survival (DFS); Univariate/multivariate analyses were conducted by logistic regression method. Results: TRG grade proved significantly worse in patients with high values of both NLR and PLR whether in univariate (OR=3.457; p=0.044) or multivariate (OR=6.876; p=0.028) analysis. Degree of tumor differentiation was an independently predictive factor for TRG (OR=2.874; p=0.037) in multivariate analysis. In subgroup analyses, NLR predicted OS (p=0.04) and DFS (p=0.03) in female patients; whereas PLR was predictive of both OS (p=0.026) and DFS (p=0.018) in patients with clinical TNM stage 3 disease and dissected lymph node counts <28. PLR similarly predicted OS in patients <65 years old (p=0.049), those with positive lymph nodes (p=0.021), or those with moderate or poorly differentiated tumors (p=0.049). Conclusion: Pretreatment NLR and PLR together serve to independently predict TRG after NCT and surgery in patients with locally advanced GC. Screening for patients with high NLR and PLR values may allow them to benefit upfront from alternatives to NCT.